(3GdcdGe aj GdTYQs - (3YHO Gddg Hf GdWjH GdHZOGOj , nCoHh GdnanQL GHf GdpqWpqjH , J (B435 (3g` s
(3ChdgG (B:s
(3GdaVdGJ GdHGbjI ef GdZPGA GdPi JJZPi HgY GdCYVGA NQHGf QWHI jGHSI s
(3BNQgG (B:s
(3Je GdcdGe ai GdTYQ hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3fSNI fajSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/4) s
Keywords: (3GdadSaI hGdefWbs